Peri-conception and first trimester diet modifies reproductive development in bulls - Copping, Katrina J.; Ruiz-Diaz, Maria Dolores; Rutland, Catrin S.; Mongan, Nigel P.; Callaghan, M.J.; McMillen, I. Caroline; Rodgers, Raymond J.; Perry, V.E.A. (CSIRO Publishing, 2017)
Nutritional perturbation during gestation alters male reproductive development in rodents and sheep. In cattle both the developmental trajectory of the feto–placental unit and its response to dietary perturbations is dissimilar to that of these species. This study examined the effects of dietary protein perturbation during the peri-conception and first trimester periods upon reproductive development in bulls. Nulliparous heifers (n = 360) were individually fed a high- or low-protein diet (HPeri and LPeri) from 60 days before conception. From 24 until 98 days post conception, half of each treatment group changed to the alternative post-conception high- or low-protein diet (HPost and LPost) yielding four treatment groups in a 2 × 2 factorial design. A subset of male fetuses (n = 25) was excised at 98 days post conception and fetal testis development was assessed. Reproductive development of singleton male progeny (n = 40) was assessed until slaughter at 598 days of age, when adult testicular cytology was evaluated. Low peri-conception diet delayed reproductive development: sperm quality was lowered during pubertal development with a concomitant delay in reaching puberty. These effects were subsequent to lower FSH concentrations at 330 and 438 days of age. In the fetus, the low peri-conception diet increased the proportion of seminiferous tubules and decreased blood vessel area in the testis, whereas low first trimester diet increased blood vessel number in the adult testis. We conclude that maternal dietary protein perturbation during conception and early gestation may alter male testis development and delay puberty in bulls.